2021
DOI: 10.15441/ceem.20.021
|View full text |Cite
|
Sign up to set email alerts
|

Use of noninvasive volume assessment methods to predict acute blood loss in spontaneously breathing volunteers

Abstract: Objective The use of noninvasive volume assessment methods to predict acute blood loss in spontaneously breathing patients remains unclear. We aimed to investigate changes in the pleth variability index (PVI), vena cava collapsibility index (VCCI), end-tidal carbon dioxide (EtCO2), pulse pressure (PP), and mean arterial pressure (MAP) in spontaneously breathing volunteers after acute loss of 450 mL blood and passive leg raise (PLR).Methods This prospective observational study enrolled healthy volunteers in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Delerme showed that the PVI value decreased significantly after passive leg raising in spontaneously breathing patients, and they concluded that PVI may be valuable in evaluating fluid response [ 13 ]. Tomo and colleagues showed that the PVI value decreased significantly after passive leg raising in spontaneously breathing patients, and they concluded that PVI could detect early hemodynamic changes after acute blood loss [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Delerme showed that the PVI value decreased significantly after passive leg raising in spontaneously breathing patients, and they concluded that PVI may be valuable in evaluating fluid response [ 13 ]. Tomo and colleagues showed that the PVI value decreased significantly after passive leg raising in spontaneously breathing patients, and they concluded that PVI could detect early hemodynamic changes after acute blood loss [ 14 ].…”
Section: Discussionmentioning
confidence: 99%